Charge Transport: Long‐Range Tunneling Processes across Ferritin‐Based Junctions (Adv. Mater. 9/2016). Issue 9 (1st March 2016) - Kumar, Karuppannan Senthil; Pasula, Rupali Reddy; Lim, Sierin; Nijhuis, Christian A.
Abstract : On page 1824, C. A. Nijhuis and co‐workers report the mechanism of long‐range (ca. 12 nm) electron transport in ferritin‐based tunnel junctions. The mechanism of charge transport switches between coherent tunneling, sequential tunneling, and hopping by iron content inside the ferritin core. This study helps to improve our understanding electron transport in biological systems. Image credit: Harshini V. Annadata.